Thermodynamic picture of terahertz conduction in graphene - Mics, Zoltan; Tielrooij, Klaas Jan; Ivanov, Ivan; Feng, Xinliang; Mullen, Klaus; Bonn, Mischa; Turchinovich, Dmitry (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2016)
The conductivity of graphene and its change induced by electromagnetic waves is crucial for many applications. Here we show that both the photoconductivity and high-field conductivity of highly doped graphene can be described by a simple thermodynamic balance maintained within the free carrier population of graphene.
CRIS-Team Scopus Importer:2023-03-20